Quality assessment of formal internal communication system from the perspective of human system audit - (HSA) - Hernández García, David; Díaz de Quijano, Santiago (Folios, revista de la Facultad de Comunicaciones y Filología, 2011)
As a structure and psychological phenomenon the organizational communication is of great importance for its ability to transcend the fields of activities and strategies at the organizational level. In this sense, the systemic approach sees the organization as a system composed by interdependent and interrelated structures seeking to achieve the institutional objectives,and the internal communication system, within the systemic approach, has been configured as the practices and procedures for the Exchange of information.